ENHANCE SECURITY IMAGE ON PASSENGER COMBINATION ALGORITHM ARNOLD CAT MAP (ACM) AND RIVEST SHAMIR ADLEMAN (RSA) - Andre Hasudungan (Jurnal Elektro dan Telkomunikasi, 2020)
At present, the security and confidentiality of the data or information is a critical thing and the increasingly widespread use of image data in a variety of fields. Therefore, the security of image data from unauthorized access becomes necessary. There are a variety of techniques to improve the safety of the data or information has been developed, one of which is Cryptography technique or so-called encryption/decryption technique. Cryptography is the science of keeping messages by changing the data or information into a form that is different or can not be recognized. To increase security on the image we can take more than one encryption algorithm, and a second cryptography algorithm to do encryption and decryption can be the way. Cryptographic algorithms commonly used today and proved its strength especially for the digital image is Algorithm with Chaos system. Arnold's Cat Map (ACM) is one of a chaos-based algorithm that can be used to encrypt the image file and to improve security on that image then use new algorithms are algorithms Rivest Shamir Adleman (RSA) algorithm, known as the standard in the field of cryptography. This research aims to optimize the security image jpg format by combining two cryptographic algorithms are algorithms ACM and the RSA algorithm so expect the strength of the encrypted with the algorithms are complicated to be solved.The aims of the comparison MSE showed good results where quality RGB original image with the image of an encrypted does not show error , but the value of PSNR between the original image with the image of the encoded still showed noise where PSNR finally to red (r) = 16.8955, green (g) = -1.9952, blue (b) = -7.1882. Comparison of the time required for each encryption-decryption is approximately 0.1 seconds to 0.4 seconds.